2017
DOI: 10.1007/s40843-017-9134-x
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in three-dimensional titanium alloy mesh scaffolds fabricated by electron beam melting for biomedical devices: mechanical and biological aspects

Abstract: We elucidate here the process-structure-property relationships in three-dimensional (3D) implantable titanium alloy biomaterials processed by electron beam melting (EBM) that is based on the principle of additive manufacturing. The conventional methods for processing of biomedical devices including freeze casting and sintering are limited because of the difficulties in adaptation at the host site and difference in the micro/macrostructure, mechanical, and physical properties with the host tissue. In this regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 172 publications
0
17
0
Order By: Relevance
“…The control of the surface morphology in hydrogels has a potential impact on the development of high-performance devices for biomedical applications, such as tissueengineered scaffolds and systems for drug delivery. Noting that surface morphology provides a unique way of controlling cell-biomaterial interaction and plays a major role in modulating cellular behaviour, such as cell attachment and proliferation during cell culture [46][47][48]. We found that by precisely varying the rotation speed of the VFD tube, PVA hydrogel films with different surface morphologies were readily fabricated.…”
Section: Resultsmentioning
confidence: 96%
“…The control of the surface morphology in hydrogels has a potential impact on the development of high-performance devices for biomedical applications, such as tissueengineered scaffolds and systems for drug delivery. Noting that surface morphology provides a unique way of controlling cell-biomaterial interaction and plays a major role in modulating cellular behaviour, such as cell attachment and proliferation during cell culture [46][47][48]. We found that by precisely varying the rotation speed of the VFD tube, PVA hydrogel films with different surface morphologies were readily fabricated.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, extrusion-based three-dimensional (3D) printing technology has been widely applied for producing biomaterials in regenerative medicine and promoted significant innovations [18][19][20][21][22]. During printing, viscoelastic inks are extruded out of a 3D printer's nozzle as printed fibers, which are deposited into patterns layer by layer when the nozzle moves [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium (Ti) and some of its alloys have been widely utilized in the medical field due to their high specific strength, excellent corrosion resistance, and biocompatibility in the human body environment [1][2][3][4][5]. However, current widely-used Ti alloys, such as extra-low interstitial (ELI) Ti-6Al-4V (wt.% hereafter), Ti-5Al-2.5Fe and Ti-6Al-7Nb, have the risk of releasing toxic aluminum (Al) and vanadium (V) ions in vivo, which can cause health-related problems, e.g., Alzheimer's disease and neuropathy [6].…”
Section: Introductionmentioning
confidence: 99%